The penetration protease of the cercariae of Schistosoma mansoni - Heussen, Christa (Division of Clinical Immunology, 2018)
This thesis is concerned with a study of the proteases released by the cercariae of Schistosoma mansoni while penetrating mammalian skin. The proteases present in secretions collected from the preacetabular glands of cercariae were shown to be active against ¹²⁵I-labelled fibrin but not against undenatured ³H-collagen. A sensitive solid phase radioenzyme assay, with ¹²⁵I-fibrin as the substrate, was used to show that the cercarial protease could be totally inhibited by serine protease inhibitors such as diisopropylfluorophosphate or phenylmethylsulfonyl fluoride, but not by the sulfhydryl reagents iodoacetamide or p-chloromercuribenzoate. Typical trypsin inhibitors such as soy bean trypsin inhibitor, trasylol or benzamidine inhibited the enzyme to a lesser degree. The active-site labels, TLCK, TPCK and AcAAAACK of trypsin, chymotrypsin and elastase respectively had no effect. Calcium and magnesium stimulated protease activity at concentrations below 0,5 mM, but inhibited at higher concentrations, whereas EDTA had no effect. The pH optimum of the protease lay between pH 9,0 and 9,5. From these studies, I have concluded that the major cercarial penetration protease is an alkaline serine protease with trypsin-like specificity, but not acting via the same mechanism. A technique was developed for examining cercarial proteases in polyacrylamide gels containing SDS and copolymerized gelatin substrate. Bands of proteolytic activity could be detected by negative staining. This method was used to show that cercarial secretions contained one major protease with a molecular weight of 35 000 and that crude enzyme preparations are readily contaminated with bacterial proteases. Partial purification of the major cercarial protease was achieved by cation exchange chromatography.